The Sympathetic Nervous System Alterations in Human Hypertension. Issue 6 (13th March 2015) - Grassi, Guido; Mark, Allyn; Esler, Murray
<x xml:space="preserve">Abstract</x> Several articles have dealt with the importance and mechanisms of the sympathetic nervous system alterations in experimental animal models of hypertension. This review addresses the role of the sympathetic nervous system in the pathophysiology and therapy of human hypertension. We first discuss the strengths and limitations of various techniques for assessing the sympathetic nervous system in humans, with a focus on heart rate, plasma norepinephrine, microneurographic recording of sympathetic nerve traffic, and measurements of radiolabeled norepinephrine spillover. We then examine the evidence supporting the importance of neuroadrenergic factors as promoters and amplifiers of human hypertension. We expand on the role of the sympathetic nervous system in 2 increasingly common forms of secondary hypertension, namely hypertension associated with obesity and with renal disease. With this background, we examine interventions of sympathetic deactivation as a mode of antihypertensive treatment. Particular emphasis is given to the background and results of recent therapeutic approaches based on carotid baroreceptor stimulation and radiofrequency ablation of the renal nerves.